Implikasi Gangguan Bunyi Kadazandusun terhadap Sebutan dan Makna Rukun Qawliyy dalam Ibadah Solat - Mohd. Taqwudin Mohd. Yazid; Mohammad Najib Jaffar; Mohd Nizwan Musling; Norazman Alias; Mohammad Ali Abdullah (Penerbit UTM Press, 2025)
Index (Tier 3)